The role of artificial intelligence in innovative management: international experience and Kazakhstan’s opportunities - S.T. Kupeshova; A. Zhidebekkyzy; U.B. Bauyrzhan; J. Wirth (Хабаршысы. Экономика сериясы)
It is widely recognized that the potential of artificial intelligence (AI) is incredibly multifaceted. With its help, tasks and services that could previously only be performed by humans are now performed quickly and efficiently using various available technologies. AI makes life much easier by effectively solving technical problems and optimizing many processes. As a key driver of the fourth industrial revolution, artificial intelligence has a profound impact on the productivity of organizations, fundamentally changing existing business models and stimulating innovation processes.